1978
DOI: 10.1039/c39780000328
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric reduction of methyl benzoylformate with a chiral NAD(P)H-model compound

Abstract: The title reaction with N-(R)-a-methylbenzyl-1-propyl-2-methyl-4-(R) -methyl-1,4-dihydronicotinarnide or its 4-(S)-methyl isomer affords methyl mandelate in 97 yo optical yield and quantitative chemical yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…119−128 The role played by a divalent metal ion such as magnesium may be the activation of the substrate and the 1,4-dihydronicotinamide, as well as the stabilization of the transition state. 129,130 mNADHs, especially MNAH, PNAH, and BNAH, have been used in the reduction of a wide range of compounds (Scheme 14), such as α-keto esters, 121,131,132 α-diketones, 133 α-hydroxy ketones, 133 trifluoroacetophenone, 134,135 benzaldehydes and acetophenone, 136 2-acylpyridines, 137 and cinnamoylpyridines (with Mg 2+ or Zn 2+ ). 138 The reduction of different imines to amines has also been carried out, with α-imino esters, 139 αimino acids, 140 α,β-unsaturated iminium salts, 141 and reductive aminations.…”
Section: Applications To Organic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…119−128 The role played by a divalent metal ion such as magnesium may be the activation of the substrate and the 1,4-dihydronicotinamide, as well as the stabilization of the transition state. 129,130 mNADHs, especially MNAH, PNAH, and BNAH, have been used in the reduction of a wide range of compounds (Scheme 14), such as α-keto esters, 121,131,132 α-diketones, 133 α-hydroxy ketones, 133 trifluoroacetophenone, 134,135 benzaldehydes and acetophenone, 136 2-acylpyridines, 137 and cinnamoylpyridines (with Mg 2+ or Zn 2+ ). 138 The reduction of different imines to amines has also been carried out, with α-imino esters, 139 αimino acids, 140 α,β-unsaturated iminium salts, 141 and reductive aminations.…”
Section: Applications To Organic Chemistrymentioning
confidence: 99%
“…mNADHs, especially MNAH, PNAH, and BNAH, have been used in the reduction of a wide range of compounds (Scheme ), such as α-keto esters, ,, α-diketones, α-hydroxy ketones, trifluoroacetophenone, , benzaldehydes and acetophenone, 2-acylpyridines, and cinnamoylpyridines (with Mg 2+ or Zn 2+ ) . The reduction of different imines to amines has also been carried out, with α-imino esters, α-imino acids, α,β-unsaturated iminium salts, and reductive aminations .…”
Section: Applications To Organic Chemistrymentioning
confidence: 99%
“…For this reason, chiral NAD(P)H model 21 was designed by Ohno's group (Figure 11). 46,47 It was found that 21 exerts high enantiospecificity in the reaction in the presence of Mg 2+ , and the ee was controlled by steric effects of substituents. The C-4 functional group played a crucial role in the transition state.…”
Section: Effect Of the C-4 Substituent Of Dihydropyridinementioning
confidence: 99%
“…[2] The second aspect was to incorporate a substituent at the reaction center: the C-4 position of the dihydropyridine ring. [3] The third one was to design the specific conformation to obtain high stereoselectivity. [4] However, in the first situation the dihydronicotinamide unit needs to be modified significantly by introducing big chiral auxiliaries, a complicated ring or by changing the amide group to a chiral sulfinyl group.…”
mentioning
confidence: 99%